Kajian Metode Aplikasi Sinkronisasi Birahi menggunakan PGF2α pada kambing terhadap kualitas estrus, konsentrasi progesterone dalam darah dan tingkat kebuntingannya - Agung Budiyanto; Faradina Kusuma Savitri; Yuda Heru Fibrianto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
A study of the application method of estrus synchronization with prostaglandin 2 alpha (PGF2α) preparations in local goats in Yogyakarta to determine the effectiveness of estrus synchronization based on the quality of estrus, the concentration of the hormone progesterone in the blood and the level of pregnancy have been done. The low pregnancy rate in goats is caused by a short time of heat and mating behavior that is not clear, resulting in low reproductive performance. The application of lust synchronization technology is expected to solve this problem. Prostaglandin F2α (PGF2α) is commonly applied in Indonesia intramuscularly (IM), while other methods have no known scientific data on the effectiveness of this method. This study used two methods, namely intramuscular (IM) as a control and intravaginal sponge (IS) method. The IM method is a standard method that is commonly used in synchronizing goat estrus, while the IS method with a smaller dose has never been studied scientifically and in detail. This study was to determine the effective dose required in the IS administration of PGF2α hormone in influencing the quality of estrus, progesterone hormone profile, and pregnancy and compared with IM application as a control. This study used 24 goats that had given birth, were not pregnant, aged 3-5 years, had an average weight of 40 kg and were healthy, divided into 3 treatment groups. Group 1 IM PGF2α hormone (8.25 mg / head), group 2 IS PGF2α hormone (5.5 mg / head) and group 3 IS PGF2α hormone (2.75 mg / head). Estrus detection was carried out by visual observation, mating using a trained male, testing progesterone levels with an ELISA kit and pregnancy examination with ultrasound. The results were analyzed using ANOVA and T-Test. The results showed that there was no difference in estrous quality (P> 0.05) at the peak of estrus in each group. Progesterone levels in the IS group with a dose of PGF 5.5 and 2.75 mg / head indicated that the dose of 5.5 mg / head was lower than that in the 2.75 mg / head group. The pregnancy rate of the IM group was not significantly different from the IS group. The conclusion of this research is that synchronization of estrus using PGF2α by IS would to be effectively produce the quality of lust, the level of progesterone in the blood and pregnancy which are not different from the IM administration. The IS method can be applied to synchronization of goats in Indonesia at a lower cost, but the level of efficiency and effectiveness is not different from the IM method which uses a higher dose.